1988
DOI: 10.1002/ajh.2830290207
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic aspects of human immunodeficiency virus infection: Laboratory and clinical considerations

Abstract: Hematologic abnormalities are common in patients with HIV infection. This review will focus on HIV-associated cytopenias and coagulation abnormalities. Their occurrence, laboratory evaluation, and clinical significance and the mechanisms underlying their development are discussed. Therapeutic modalities are presented, with an emphasis on treatment strategies for HIV-associated thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 95 publications
0
30
0
4
Order By: Relevance
“…We used ketamine for viral or saline inoculation, blood sampling, and autopsy. Ketamine has safely been used for bone marrow aspiration in humans and monkeys (21,22,26,34,35). It would be unlikely, therefore, that such bone marrow suppression occurred as a result of the anesthetic agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used ketamine for viral or saline inoculation, blood sampling, and autopsy. Ketamine has safely been used for bone marrow aspiration in humans and monkeys (21,22,26,34,35). It would be unlikely, therefore, that such bone marrow suppression occurred as a result of the anesthetic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a few reports have shown that the bone marrow of patients with AIDS displays morphological alterations similar to those of patients with myelodysplastic syndrome (2,31). The term "HIV myelopathy" has been used for this bone marrow pathology by some investigators (10,22).…”
mentioning
confidence: 99%
“…Anemia is a common manifestation in patients with human immunodeficiency virus infection 25,28 . The degree of anemia in patients with CDC-defined AIDS is usually mild with a mean hemoglobin level ranging from 9.0 to 11.0 g/dL 8,25,28 .…”
Section: Discussionmentioning
confidence: 99%
“…While several studies 2123 " 26 have compared similar bone marrow findings in HIV-infected patients to those seen in myelodysplastic syndrome, others have found no characteristic dysplastic bone marrow features in these patients. 6,12,19,24,27 In this study, mild to moderate dyserythropoiesis was seen in 44% of the bone marrow, but myelodysplasia of all cell lines was an uncommon finding. The dysplasia that was seen in the bone marrow of the three patients with lymphomas may not have been directly caused by HIV infection.…”
Section: Discussionmentioning
confidence: 49%